EXPRESSION OF GH GENE POLYMORPHISMS AND THEIR ASSOCIATION WITH GROWTH TRAITS OF LOCAL, EXOTIC BREED AND THEIR RECIPROCAL CROSSBRED CHICKENS USING MOLECULAR MARKERS - Ahmed, Lajan; Abdullah, Mohammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimedto characterize by using two genetic groups of chickens, which were Kurdish indigenous chickens (KK) and commercial Super Harco chickens which bred particularly for dualpurpose (SS),Four combinations were produced by diallel crossing between the two genotypes which are (KK, KS, SK, and SS).. The single nucleotide polymorphisms (SNPs) in the GH genes were identified between genotypes. Additionally, assessment oftheir belong to genotypes relationships with growth efficiency (body weight (BW) at hatching and 3,6,9, 12 weeks of age was carried on. The four genotypes were detected by using polymerase chain reaction- restriction fragment length polymorphism (PCR-RFLP) techniques by specific primers and restrictase for GH gene.Our data showed that the AA genotype had more values in KK and SK chickens while AB genotype were more in values in KS. The genotype BB was only more in SS (0.56) birds and no values in KK (0.04), KS (0.25) and SK (0.09) birds. The analysis of chi-square test indicated that SK, SS, males and femaleswhich arein (HWE) Hardy-Weinberg equilibrium (p<0.05). The statistical analysis showed that significantcorrelations (p < 0.05) between the GH and the following parameters: BW at 3, 6, 9 and 12 weeks of age, it was determined that the hetrozygotes AB genotype values were superior in BW (39.00± 0.37 kg) and (38.50± 0. 70 kg) in KS * Male and KS * Female respectively at hatching. On the other hand, KK * Female with AA genotype had the lowest body weight (31.60e ± 0.50, 219.00e ± 2.45, 456.60g ± 1.64, 752.00e ± 1.70 and 1087.00g ± 1.48) kg at day one, 3,6,9 and 12 weeks of age respectively compared to other genotypes. Based on the findings of this study, we proposed that in pure and crosses lines chicken population selection programs, a candidate gene marker for chicken growth characteristics could be the GH gene.